Board Game Development to Improve College Students' Conflict Management - Caraka Putra Bhakti; Caraka Putra Bhakti; Difa Ardiyanti; Tasya Amin Zakiyah; Difa Ardiyanti (Universitas Negeri Malang, 2026)
The low conflict management skills of students impact psychological aspects and interpersonal relationships. This study aims to develop a learning medium in the form of a board game as a means to improve students' conflict management skills. The method used is Research and Development (R&D) with the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. In the analysis stage, data were obtained from 316 students, which showed that most were in the category of medium and low conflict management skills. The design stage was carried out by referring to the Thomas-Kilmann model, which includes five conflict management styles. The developed product was then validated by material, media, and service experts using the Aiken index. Next, the board game was implemented in guidance activities with a pretest and posttest design to measure its effectiveness. The results of the study indicate that the developed board game is suitable for use as a learning medium and has the potential to improve students' communication, negotiation, and conflict resolution skills. Thus, board games can be an innovative alternative in guidance and counselling services in higher education.